The Clue In The Jewel Box - Keene Carolyn; Carolyn Keene (New York Carolyn Keene, 1943)
Nancy helping exiled Madame Alexandra locate her long-lost grandson, Prince Michael, using a faded photo
Keywords: duty, the consequences of social prejudice, and the exposure of deceit; honesty, the danger of superficial judgments, and the enduring importance of family